Textual Analysis of Nike’s Dream Crazy Commercial - Khushaim, Mohammed (Eximia, 2022)
In 2018, Nike Inc. chose Colin Kaepernick as the face of the "Just Do It" campaign to celebrate its 30th anniversary. Due to Kaepernick's scandalous past of kneeling during the national anthem, the controversial decision represented an excellent risk for Nike as a brand. This paper depicts that even though Nike's stocks eventually recovered, the evidence shows that political stances impact a company's profitability. Often, the impact is negative in the short term since customers tend to always divide between the two sides of every significant socially or politically contentious matter.